Biolistic transformation of oil palm using the phosphomannose isomerase (pmi) gene as the positive selectable marker / Bahariah Bohari - Bohari, Bahariah (2010)
The selectable marker system based on the Escherichia coli phosphomannose isomerase (pmi) gene was adapted for genetic transformation of oil palm. This system makes use of the pmi gene that encodes phosphomannose isomerase, which converts mannose-6-phosphate to fructose-6-phosphate and uses mannose as the selection agent. This is to anticipate the future requirement of using non-antibiotic resistance genes for the commercialization of transgenic oil palm. The use of antibiotic or herbicide-based selection systems has caused much public concern due to inadequate knowledge of the agents’ impact on the environment and on human health. In this study, four transformation vectors, namely pMI3, pMI11, pMI3G and pMI11G were constructed for transforming oil palm. The pmi gene is driven by CaMV35S promoter in pMI3 and pMI3G, and Ubi1 promoter in pMI11 and pMI11G. gusA gene was also included in the pMI3G and pMI11G constructs. The gene constructs were transferred into oil palm embryogenic calli via biolistic-mediated transformation. Bombarded calli were selected on medium supplemented with mannose as a carbon source. Results from kill curve experiment indicated that oil palm embryogenic callus have little or no PMI activity and cannot utilize mannose as a carbon source. However, when calli were transformed with a pmi gene, the PMI activity was greatly increased and they could utilize mannose efficiently as carbon source. For early identification of transgenic events, histochemical staining with 5-bromo-4-chloro-3-indolyl-ß-D-glucuronide (X-Gluc) was used. Transgenic plants were confirmed by PCR and the transgene expression was detected using RT-PCR analysis. Transient expression results demonstrate that the Ubi1 promoter is more efficient than the CaMV35S promoter in oil palm embryogenic calli. The insertion verification was confirmed with 98% homology observed to its corresponding pmi gene from E. coli (Genbank accession no: M15380) via PCR direct sequencing. In conclusion, the results of this study indicated that mannose selection system can be used for oil palm transformation. Potentially this will make transgenic oil palm acceptable in the future.